Interleukin‐8 and CXCL10 expression in oral keratinocytes and fibroblasts via Toll‐like receptors. (14th March 2013) - Fukui, Akiko; Ohta, Kouji; Nishi, Hiromi; Shigeishi, Hideo; Tobiume, Kei; Takechi, Masaaki; Kamata, Nobuyuki
ABSTRACT Oral keratinocytes and fibroblasts may be the first line of host defense against oral microorganisms. Here, the contention that oral keratinocytes and fibroblasts recognize microbial components via Toll‐like receptors (TLRs) and participate in development of oral inflammation was examined. It was found that immortalized oral keratinocytes (RT7), fibroblasts (GT1) and primary cells express mRNA of TLRs 1–10. Interleukin‐8 (IL‐8) production by RT7 cells was induced by treatment with TLRs 1–9 with the exception of TLR7 agonist, whereas GT1 cells were induced to produce IL‐8 by all TLR agonists tested except for TLR7 and TLR9. GT1 cells showed increased CXCL10 production following treatment with agonists for TLR1/2, TLR3, TLR4, and TLR5, whereas only those for TLR3 and TLR5 increased CXCL10 production in RT7 cells. Moreover, TLR agonists differentially regulated tumor necrosis factor‐alpha‐induced IL‐8 and CXCL10 production by the tested cell types. These findings suggest that recognition of pathogenic microorganisms in oral keratinocytes and fibroblasts by TLRs may have important roles in orchestrating host immune responses via production of various chemokines.